2017
DOI: 10.3389/fpls.2017.01907
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Metabolome Analyses Provide Insights into the Occurrence of Peel Roughing Disorder on Satsuma Mandarin (Citrus unshiu Marc.) Fruit

Abstract: Roughing disorder (RD) is a significant quality barrier in citrus fruit, prevalent on easy-peeling mandarins. As RD is not yet well-understood, this study aimed to examine the changes and synergic molecular processes involved in peel RD. Peel with RD was induced by severely defruiting Satsuma mandarin trees. Morphology observations, RNA-sequencing, and targeted and untargeted metabolic analyses were conducted. The results showed that the primary metabolites of sugars, organic acids and amino acids are dramatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Of the other key differences, changes in cell wall composition seemed to be dominant since, in almost all of the treatment comparisons (except C5 vs. D4 in transcriptome), we observed the differential regulation of related genes and accumulation of related metabolites (Supplementary Tables 3-5). This observation is consistent with a previous study on the differential accumulation of cell wall-related metabolites and changes in cell wall thickness in mandarins (Lu et al, 2017). In this regard, the exclusive expression of XTH22 and XTH24 is quite relevant to the visible phenotype of D, i.e., thicker peel (Supplementary Tables 3, 5).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Of the other key differences, changes in cell wall composition seemed to be dominant since, in almost all of the treatment comparisons (except C5 vs. D4 in transcriptome), we observed the differential regulation of related genes and accumulation of related metabolites (Supplementary Tables 3-5). This observation is consistent with a previous study on the differential accumulation of cell wall-related metabolites and changes in cell wall thickness in mandarins (Lu et al, 2017). In this regard, the exclusive expression of XTH22 and XTH24 is quite relevant to the visible phenotype of D, i.e., thicker peel (Supplementary Tables 3, 5).…”
Section: Discussionsupporting
confidence: 93%
“…The authors reported that sugars, organic acids, and amino acids and derivatives were the main metabolites that were differentially accumulated. Particularly, the amino acids and derivatives accumulated in higher quantities in the RD peels (Food and Agriculture Organization, 2017;Lu et al, 2017). The authors of a latest study only considered the peels of fruits at 170 days after full bloom, thus, leaving a knowledge gap between the early developmental stages of the citrus peels (Lu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, multiomics integration analysis has been applied to study plant development 2729 , environmental responses 3033 , and other biological processes 3436 . Specifically, transcript and metabolite datasets have been analyzed and compared, integrated through correlation and cluster analyses and ultimately used to reveal the relationships between genes and metabolites in Arabidopsis 30,35,37,38 and fruit trees such as citrus 29,32,39 , grape 40,41 , kiwifruit 42 , lichi 43 and fig fruit 44 trees. Integrated analysis of “omics” datasets (i.e., transcriptome and metabolome) can provide an effective strategy for identifying potential genes regulating light-induced anthocyanin biosynthesis in red Chinese sand pear.…”
Section: Introductionmentioning
confidence: 99%
“…The development of fruit skin thickness in the two varieties is in accordance with the phase of growth and development which is differently intervals for each variety. According to Lu et al (2017), in Satsuma Mandarin the development of fruit is characterized by the increase of diameter size along with the thickening of fruit skin until the age of 30 days. Then with increasing age, the size of the fruit increases but the thickness of the skin decreases until the ripening phase.…”
Section: Resultsmentioning
confidence: 99%